Neurofibrosarcoma in a blue-fronted amazon-parrot (Amazona aestiva) - Case report - Pachaly, José Ricardo (2016)
ABSTRACT. Pachaly J.R., De Conti J.B., Werner P.R., Sanches A.W.D., Montiani-Ferreia F., Santos A.L.Q., Germano R.M. & Voltarelli-Pachaly E.M. [Neurofibrosarcoma in a blue-fronted amazon-parrot (Amazona aestiva) - Case report.] Neurofibrossarcoma em papagaio-verdadeiro (Amazona aestiva) - Relato de caso. Revista Brasileira de Medicina Veterinária, 38(Supl.1):115-119, 2016. Programa de Pós-Graduação em Ciência Animal, Universidade Paranaense, Campus Umuarama, Praça Mascarenhas de Moraes, 4282, Zona III, Umuarama, PR 87502-210, Brasil. E-mail: pachaly@uol.com.br In 2002, a 22-year old 0.3 kg blue-fronted amazon parrot (Amazona aestiva) legally kept as a pet presented a large tumor in the left cervical submandibular area. Surgery was indicated and the bird was anesthetized with IM ketamine (80 mg/kg) and xylazine (8 mg/kg). The subcutaneous tumor had poor blood supply and was easily excised. Major vessels were ligated and subcutaneous tissue and skin were closed with #3.0 catgut. After closing the skin a slight layer of cyanoacrylate glue was applied, as an additional protection against self-injuring. Seven days after the surgery the parrot was in good physical conditions and the sutures were removed. Histologically, the neoplasm consisted of interwoven bundles and whorls of elongated cells with spindle-shaped nuclei and moderate collagen production. The neoplastic cells showed discrete signs of anaplasia such as pleomorphism, anisocaryosis, atypical nuclei and mitotic index of up to three mitotic figures per high power field. Occasional necrotic foci were seen, sometimes bordered by palisading neoplastic cells resembling Verocay bodies. Due to its resemblance to peripheral nerve-sheath cells, histochemical special stain for S-100 protein was made, which resulted negative. The diagnosis was low-grade neurofibrosarcoma, a very rare neoplasm in psittacine birds. The patient was examined again 154 months after the surgery, and no signs of neoplasia were seen.